A Work study on Hinabi Knitwear Incorporated - Lopez, Marco Vincent; Pascual, Paul Maria; Rosete, Patricia Ann; Yumul, Myleen (College of Engineering, 1992)
Hinabi Knitwear Incorporated (HK) has started business last August of 1989, and up until today, HK is still selling knitted blouses to department stores and personal customers all over Metro Manila. Being a young manufacturing company, HK is very vulnerable to various kinds of problems occuring within a firm. This would be enough reason for Industrial Engineering students to start an intensive study about HK. Our group in IE 32, which consists of Marco Lopez, Paul Maria Pascual, Patricia Ann Rosete and Myleen Yumul, has started a comprehensive study on HK last December of 1991. We made a four (4) step plan of action for our study so that we will not deviate from our objectives. Our plan of action involves the following : Step 1 : Familiarization with the company. Step 2 : Search for possible problem areas. Step 3 : Quantitative and qualitative analysis of problems. Step 4 : Search for the best solutions. The first step consisted of getting to know the management and the workers. Fortunately, people in HK were very cooperative. The second step took us the longest time to accomplish. It consisted of the documentation of the existing system of HK. The documentation involved interviews with the management and the workers, actual observation of procedures, and the use of files of the company. From the data we collected, we were able to identify problem areas within HK.During our data collection, the company experienced a slack period in production. This was a problem for our group since we would not be getting the appropriate statistics, especially in our work sampling. We had to wait for a week and a half for the company to get back to regular production. During the third step, after we located the problem areas of the company, we found out that seventeen to twenty eight percent (17 to 28 percent) of working time of each worker is spent unproductively. This would be an hour and a half (1.5) to two (2) hours of unproductive time during a nine (9) hour working day. Our group also found out that many additional costs were incurred through improper management and use of resources such as the carrying costs of unrecorded inventory, machine repair due to lack of maintenance, ambiguous forms and unproductive time spent by workers. To solve these problems, we proposed several alternatives. These composes the last step of our study. Our recommendations incur a total cost P1,160,124.00. However, total benefits of P2,085,305.00, outweigh these costs.